Health state utilities associated with caring for an individual with cutaneous T-cell lymphoma (CTCL). (2nd October 2020) - Williams, Kate; Gibson, Adam; McNamara, Linda; Jones, Trefor; Lloyd, Andrew J.
Abstract: Aim: Cutaneous T-cell Lymphoma (CTCL) is a rare form of non-Hodgkin lymphoma characterized by skin lesions, which can negatively impact the quality of life of both patients and their caregivers. The Decision Support Unit (DSU) at the National Institute for Health and Care Excellence (NICE) in the UK recently outlined a rationale for the inclusion of caregiver burden in economic evaluations. This study aimed to estimate utilities for health states associated with being a caregiver for an individual with CTCL at different stages of treatment. Materials and methods: A targeted literature review and interviews with CTCL specialists informed the development of health state vignettes describing the experience caring for an individual with CTCL. The vignettes were evaluated in interviews with the UK general population using a visual analogue scale (VAS), the time trade-off (TTO) method and the EQ-5D-5L. Results: Four vignettes were developed describing the caregiver experience for an individual with CTCL on i) second line treatment, ii) third line treatment, iii) end of life care, iv) a post-patient death. One hundred interviews were conducted to evaluate the health state vignettes. The pattern of results was similar across the evaluation methods: second line treatment (VAS: 39.2, TTO = 0.52, EQ-5D-5L: 0.56), third line treatment (VAS: 31.1, TTO = 0.39, EQ-5D-5L: 0.37), end of life care (VAS: 28.2, TTO = 0.37, EQ-5D-5L: 0.31) and post-patient death (VAS: 41.2, TTO = 0.63, EQ-5D-5L: 0.59). Limitations and conclusions: These findings highlight the substantial burden of caring for an individual with CTCL and the importance of including caregiver burden in the health technology assessment review process. A limitation is the hypothetical vignette approach, which meant the TTO participants did not have experience of caring for individuals with CTCL, but were imagining this state. There is also the possibility that they may also be considering the patient experience when responding to the questions.